Molecular data and morphological characters clarify the taxonomic status of Pintara heringi pieridoides (Liu & Gu, 1994) (Hesperiidae, Pyrginae) - Li, Meng; Lu, Ke; Cui, Ying; Liu, Haiwei; Yang, Jinchu; Xue, Guoxi; Wang, Qiuling (Zootaxa, 2024)
We found Albiphasma heringi (Mell, 1922) and A. pieridoides (Liu & Gu, 1994) to be conspecific by the 658 bp COI gene sequences and male genitalia characters. Considering the distinguishable wing patterns and allopatric distribution of the two taxa, we treat pieridoides as a subspecies of heringi. Therefore, the genus Albiphasma Huang, Chiba, Wang and Fan, 2016, which was established for heringi and pieridoides, becomes monotypic, and in light of morphological similarities and close genetic distance between heringi and Pintara bowringi (Joicey & Talbot, 1921), we propose its synonymy with Pintara Evans, 1932. The adults and male genitalia of both P. heringi heringi (Mell, 1922) and P. heringi pieridoides (Liu & Gu, 1994) are illustrated.